Urinary strong ion difference is a major determinant of plasma chloride concentration changes in postoperative patients - Masevicius, Fabio Daniel (Associação Brasileira de Medicina intensiva, 2013)
OBJECTIVE: To show that alterations in the plasma chloride concentration ([Cl(-)](plasma)) during the postoperative period are largely dependent on the urinary strong ion difference ([SID](urine)=[Na+](urine)+[K+](urine)-[Cl-](urine)) and not on differences in fluid therapy. METHODS: Measurements were performed at intensive care unit admission and 24 hours later in a total of 148 postoperative patients. Patients were assigned into one of three groups according to the change in [Cl(-)](plasma) at the 24 hours time point: increased [Cl(-)](plasma) (n=39), decreased [Cl(-)](plasma) (n=56) or unchanged [Cl(-)](plasma) (n=53). RESULTS: On admission, the increased [Cl(-)](plasma) group had a lower [Cl(-)](plasma) (105±5 versus 109±4 and 106±3mmol/L, p<0.05), a higher plasma anion gap concentration ([AG](plasma)) and a higher strong ion gap concentration ([SIG]). After 24 hours, the increased [Cl(-)](plasma) group showed a higher [Cl(-)](plasma) (111±4 versus 104±4 and 107±3mmol/L, p<0.05) and lower [AG](plasma) and [SIG]. The volume and [SID] of administered fluids were similar between groups except that the [SID](urine) was higher (38±37 versus 18±22 and 23±18mmol/L, p<0.05) in the increased [Cl(-)](plasma) group at the 24 hours time point. A multiple linear regression analysis showed that the [Cl(-)](plasma) on admission and [SID](urine) were independent predictors of the variation in [Cl(-)](plasma) 24 hours later. CONCLUSIONS: Changes in [Cl(-)](plasma) during the first postoperative day were largely related to [SID](urine) and [Cl(-)](plasma) on admission and not to the characteristics of the infused fluids. Therefore, decreasing [SID]urine could be a major mechanism for preventing the development of saline-induced hyperchloremia.